(untitled) (Journal of Global Accounting, 2025)
This study investigates the influence of grey directors on earnings management in Nigerian publicly traded manufacturing firms. Grey directors, often considered as independent directors with some affiliations, play a crucial role in corporate governance by potentially mitigating earnings manipulation. This research utilizes a combination of theoretical and empirical reviews to explore the effects of grey directors’ independence and size on earnings management. The study employs ex post facto research design and a sample of 13 Deposit Money Banks (DMBs) listed on the Nigerian Exchange Group (NGX) were selected. The study utilises secondary data from annual financial reports which were analysed using Fixed Effects Model. The results showed a positive effect of board size on the discretionary accruals proxy for earnings management; and a non-significant negative effect of grey directors’ independence on earnings management of quoted DMBs. The study concludes that grey directors’ significantly affect financial reporting quality. The study recommends that companies carefully consider the balance of grey directors’ independence on the board and ensure that they possess the necessary industry expertise and training to fulfill their oversight responsibilities effectively. Secondly, shareholders should carefully consider the appropriate size and composition of the board. It is recommended that companies assess the specific needs of their industry, company size, and complexity to determine the optimal board size and composition. These insights suggest that improving board effectiveness might require more than just increasing the number of non-executive directors; it might also involve enhancing the independence and authority of these directors to ensure robust oversight and reduce earnings management.